Impurezas magnéticas em ferromagnetos de Ising com campo transverso - Leite Filho, Raimundo Valmir (2005)
A Green function formalism is used to calculate the spectrum of excitations associated with magnetic impurities implanted in a ferromagnetic thin film described by the transverse Ising model. Using the equations of motion method, explicit expressions for the Green function are determined for a ferromagnetic without impurities. The Green’s functions for a ferromagnetic film containing impurities are obtained through Dyson equation. We consider only the “defect” modes that appear below the bulk band of the pure material. In order to assess the influence of the position of the impurities in the film on the excitations spectra, we consider three different geometrical arrangement for the impurities: impurities line perpendicular to the surface film, four impurities in a plane paralel to the surface, and four impurities in a plane perpendicular to the surfaces of the film. We obtain results for the frequencies localized modes as a function of the exchange parameter between two impurities neighborings, of the exchange parameter between the impurities and their neighborings, and the effective field parameter at the impurities.